Toxic sustainable companies: a critique on the shortcomings of current corporate sustainability ratings and a definition of 'financial toxicity'. (3rd April 2017) - Seele, Peter; Chesney, Marc
ABSTRACT: Building on critical literature on corporate sustainability, we add a perspective thus far only scarcely addressed: the toxicity of financial practices and products generating systemic risk. We start with illustrative examples setting the stage for defining toxic assets and practices as revealed after the onset of the financial crisis precipitated by the collapse of Lehman Brothers. To illustrate corporate toxicity we use the 'Global 100 Index' from 'Corporate Knights' to show which (mostly financial) scandals or bailout cases were detected at corporations awarded a position in this prestigious sustainability rating. Next, we present examples of toxic products (Naked Credit Default Swaps and structured products) and practices (securitization and ratings). Based on the examples we derive the concept of 'financial toxicity' adopted from pharmacology as a meta-criterion, which, as we argue, should be added to the ESG (environment, society, governance) universe as well as to corporate social responsibility and Corporate Sustainability. We define financial toxicity as 'the degree to which financial products can systematically harm their buyers and, on a large scale, the extent to which these products or financial practices generate systemic risk'. We discuss implications for theory development and the overall credibility of corporate sustainability ratings.